Strength Training to Contraction Failure Increases Voluntary Activation of the Quadriceps Muscle Shortly After Total Knee Arthroplasty: A Cross-sectional Study. (March 2016) - Mikkelsen, Elin Karin; Jakobsen, Thomas Linding; Holsgaard-Larsen, Anders; Andersen, Lars Louis; Bandholm, Thomas
ABSTRACT: Objective: The objective of this study was to investigate voluntary activation of the quadriceps muscle during one set of knee extensions performed until contraction failure in patients shortly after total knee arthroplasty. Design: This was a cross-sectional study of 24 patients with total knee arthroplasty. One set of knee extensions was performed until contraction failure, using a predetermined 10 repetition maximum loading. In the operated leg, electromyographic (EMG) activity of the lateral and medial vastus, semitendinosus, and biceps femoris muscles was recorded during the set. Muscle activity (%EMGmax) and median power frequency of the EMG power spectrum were calculated for each repetition decile (10%–100% contraction failure). Results: Muscle activity increased significantly over contractions from a mean of 90.0 and 93.6 %EMGmax (lateral vastus and medial vastus, respectively) at 10% contraction failure to 99.3 and 105.5 %EMGmax at 100% contraction failure ( P = 0.009 and 0.004). Median power frequency decreased significantly over contractions from a mean of 66.8 and 64.2 Hz (lateral vastus and medial vastus, respectively) at 10% contraction failure to 59.9 and 60.1 Hz at 100% contraction failure ( P = 0.0006 and 0.0187). Conclusion: In patients shortly after total knee arthroplasty, 10 repetition maximum–loaded knee extensions performed in one set until contraction failure increases voluntary activation of the quadriceps muscle during the set. Clinical Trials: Gov-identifier: NCT01713140 to the abstract to increase trial transparency. Abstract : Supplemental digital content is available in the text.